2017
DOI: 10.1016/j.cels.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

CTCF-Mediated Chromatin Loops between Promoter and Gene Body Regulate Alternative Splicing across Individuals

Abstract: The CCCTC-binding factor (CTCF) is known to establish long-range DNA contacts that alter the three-dimensional architecture of chromatin, but how the presence of CTCF influences nearby gene expression is still poorly understood. Here, we analyze CTCF chromatin immunoprecipitation sequencing, RNA sequencing, and Hi-C data, together with genotypes from a healthy human cohort, and measure statistical associations between inter-individual variability in CTCF binding and alternative exon usage. We demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 54 publications
5
101
0
1
Order By: Relevance
“…1, S1D). Such regulatory consequences are likely to be locus-specific and idiosyncratic (Ruiz-Velasco et al, 2017). Indeed, it is fascinating that 5,886 gene promoters are equipped with a functional CTCF site, such as CTCF11 at PPARD and CTCF16 at RPL10A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1, S1D). Such regulatory consequences are likely to be locus-specific and idiosyncratic (Ruiz-Velasco et al, 2017). Indeed, it is fascinating that 5,886 gene promoters are equipped with a functional CTCF site, such as CTCF11 at PPARD and CTCF16 at RPL10A.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that, beyond helping to compact the genome, the intragenic CTCF sites may also facilitate mechanistic aspects of gene expression control such as bringing together gene promoters and enhancers (eg; Fig. S1D), or marking alternative exon usage (Ruiz-Velasco et al, 2017). Thus, 'intragenic' CTCF sites are likely to contribute to the formation of CTCF-determined chromosome topology together with 'intergenic' CTCF sites.…”
Section: Intragenic Tad Boundaries and Ctcf Site Orientationsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTCF ChIP-seq studies have found that approximately 30% and 50% of CTCF binding sites are located in intronic and intergenic regions, respectively [2,5,9]. It has been shown that the intragenic localization of CTCF binding sites influences pre-mRNA splicing decisions leading to alternative exon splicing [20,21,25]. To determine whether Ctcf binding sites are enriched in the proximity of retained introns in liver, we analyzed a publicly available ChIP-seq data set from C57BL/6 normal mouse liver (E-MTAB-5769) [42].…”
Section: Enrichment Of Ctcf Binding Sites Proximal To Differentially mentioning
confidence: 99%
“…Compelling evidence has linked CTCF to alternative splicing (AS) regulation due to its direct or indirect role in modulating splicing decisions via complex mechanisms including RNA Polymerase II (Pol II) elongation, transcriptional regulation of splicing factors, DNA methylation and chromatin organization [20][21][22][23][24][25]. Despite its potential importance, the impact of altered CTCF dosage on AS has not been investigated at a global scale.…”
Section: Introductionmentioning
confidence: 99%